Post-retrenchment and Retirement of Mineworkers: A Poor Quality of Life in Transkei Region of South Africa - B Meel (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Former mineworkers are sandwiched between scare resources and little hope of getting re-employment. They do not have enough savings to maintain their families. The expenditure is at its highest when they return from the mines, as the children are grown up and are in secondary or senior secondary school. Many are not re-employable because of poor health, and some are disabled.Objective: To highlight the problem of retrenched mineworkers in the Transkei region of South Africa.Method: The case histories of these mineworkers were recorded either at Benefit Examination Clinic (BEC) or at the forensic pathology laboratory which is situated in the chest section of the Mthatha Hospital, Mthatha.Results: There were 2027 former mineworkers examined at BEC between 1997 and 2000. Of these, 172 (8.48%) were re-examined and only 51 (2.5%) received compensated over the period of four years. The examination of mineworkers has decreased from 1997 (29.6%) to 2000 (3.94%). There were 55 (2.71%) died before they received their benefit of examination.Conclusion: Retrenched mineworkers are frequently under psychosocial pressure, including their families and the community. Extreme poverty, sickness, and disabilities co-exist among these retrenched, retired mineworkers in the Transkei region of South Africa.